Effect of communication skills training on outcomes in critically ill patients with life-limiting illness referred for intensive care management: a before-and-after study. Issue 1 (28th June 2017) - Orford, Neil R; Milnes, Sharyn; Simpson, Nicholas; Keely, Gerry; Elderkin, Tania; Bone, Allison; Martin, Peter; Bellomo, Rinaldo; Bailey, Michael; Corke, Charlie
Abstract : Objectives: To describe the effect of a communication skills training programme on patient-centred goals of care documentation and clinical outcomes in critically ill patients with life-limiting illnesses (LLI) referred for intensive care management. Methods: Prospective before-and-after cohort study in a tertiary teaching hospital in Australia. The population was 222 adult patients with LLI referred to the intensive care unit (ICU). The study was divided into two periods, before (1 May to 31 July 2015) and after (15 September to 15December 2015) the intervention. The intervention was a 2-day, small group, simulated-patient, communication skills course, and process of care for patients with LLI. The primary outcome was documentation of patient-centred goals of care discussion (PCD) within 48 hours of referral to the ICU. Secondary outcomes included clinical outcomes and 90-day mortality. Results: The intervention was associated with increased documentation of a PCD from 50% to 69% (p=0.004) and 43% to 94% (p<0.0001) in patients deceased by day 90. A significant decrease in critical care as the choice of resuscitation goal (61% vs 42%, p=0.02) was observed. Although there was no decrease in admission to ICU, there was a significant decrease in medical emergency team call prevalence (87% vs 73%, p=0.009). The cancer and organ failure groups had a significant decrease in 90-day mortality (75% vs 44%, p=0.02; 42% vs 16%, p=0.01), and the frailty group had a significant decrease in 90-day readmissions (48% vs 19%, p=0.003). Conclusions: The intervention was associated with increased PCD documentation and decrease in the choice of critical care as the resuscitation goal. Admissions to ICU did not decrease, and although limited by study design, condition-specific trajectory changes, clinical interventions and outcomes warrant further study.